Using Organizational Communication in Teaching at the Primary School - Hutasuhut, Sartika; Mesiono, Mesiono; Isa, Muhammad; Khurniawan, Deni; Suyatmika, Yulita (Universitas Pahlawan Tuanku Tambusai, 2023)
This study uses a qualitative research method with a phenomenological approach. The phenomenological approach of the researcher tries to understand the meaning of various events in a certain setting with the perspective of the researcher himself. The use of this approach begins with silence, shown to examine what is being learned. The research was conducted at the Baja Kuning MIS, Langkat Regency, which is located in Baja Kuning Village. The application of the principal's Islamic communication to teachers, staff and students at MIS Baja Kuning has been implemented but has not been smooth and effective. Because in his leadership, the principal issued policies using downward communication, meaning that communication flows from superiors to subordinates. Likewise policies regarding lesson planning, implementation and evaluation of learning, school principals in the application of Islamic communication tend to use authoritative and consultative benevolent systems. Where in this pattern, sometimes the principal uses one-way communication, sometimes the principal as a place for consultation from subordinates, a place to issue/plan all ideas, opinions and ideas for the progress of the school.